Maintenance approach of heritage building in Malaysia / Mohamad Faizol Musa - Musa, Mohamad Faizol (Faculty of Architecture, Planning and Surveying, 2013)
The conservation of historical buildings is a way to preserve a heritage building structure through a maintenance work. Maintenance work can be identified as an important element to maintain the condition of the building and to protect the heritage building from damaged. The heritage building condition should be maintained and this research will be carrying out of the maintenance approach work to the heritage building. This research would to highlight the maintenance approach of heritage building in Malaysia, especially at Kuala Lumpur. Kuala Lumpur have a many heritage building was gazetted under Jabatan Warisan Negara and the structural of the building unique, have a different character and historical of building. The findings in this research are summarized from the respondent directly from the management of the heritage building and the staffs. Case studies in this paper involving 3 number of heritage building under department of heritage building will be carried out. The methodology for this research depend on self-developed questionnaire referred to the maintenance approach of the heritage building in Malaysia .The output from this research later would be know the maintenance approach to the heritage building.